Enhancing leadership integrity effectiveness strategy through the institutionalization of an organizational management integrity capacity systems / José G. Vargas-Hernández … [et al.] - Vargas-Hernández, José G.; de León-Arias, Adrián; Valdez-Zepeda, Andrés; Castillo-Girón, Víctor (Faculty of Administrative Science and Policy Studies, 2012)
This paper aims to analyze organizational management integrity capacity system as an improvement concept for enhancing leadership integrity effectiveness in a university setting. It departs from the analysis of the current organizational culture, values, virtues, managerial capabilities and attitudes to assume any organizational task. This paper aims also to propose a strategic model for the institutionalization of an organizational management integrity system. Study design: Cross-sectional study. Place and Duration of Study: University Center for Economic and Managerial Sciences, University of Guadalajara. The study is conducted for one academic year during the term 2011-2012. Methodology: The research methods used are the analytical based in the literature review and interpretative of the main findings to provide a synthetic model. Results and conclusion: The outcomes of the research on the application of organizational management integrity capacity systems may demonstrate that the drama of leadership effectiveness is centered on dysfunctional organizational integrity culture and leadership. This chapter provides a sound strategies and institutionalization for organizational integrity capacity philosophy focused on leadership integrity effectiveness that empowers management professionals to act with integrity and supported by an organizational integrity culture. Implications: The results provide the basis to develop strategies for an organizational integrity leadership framed by an organizational integrity culture, sustained by a code of conduct, regulation policies and overall the development and institutionalization of an organizational integrity capacity system which can positively influence the behavior of key stakeholders and actors.